Entre idéologie politique et identité étatique : un gouvernorat de la province umayyade d’Irak, le cas de Ziyād b. Abīh - Massaoud Kouri (Revue des Mondes Musulmans et de la Méditerranée)
The Arab-Islamic State is founded on the distribution of power by alliance between families, administering provinces or participating in central power. Some families transmit and retain their skills from one generation to the next. This is the case of the Ziyādits. Ziyād b. Abīh – a statesman and a great innovator under the Umayyads, called “king of the East” by some historians – adopts a policy contributing to the rooting of a state culture by remarkably reducing the tribal structures. Ziyād was able to transmit to his sons a state, administrative and political culture that guarantees the control of the eastern part of the empire. After an eclipse following the fall of the Umayyads, the Ziyādits are recalled to power by the Abbasids who had been their enemies : the new masters of the state require their technical skills and political weight. The family context was thus a fundamental structure of power both at the center of the empire and the provinces. The transmission of know-how for the preservation of power, the history of families and that of states interact and even overlap.